Sistem penglihatan optik untuk aplikasi robotik dan automasi - Arshad, Mohd Rizal (Universiti Sains Malaysia, 2003)
An image ocquisition system, which is used to capture 2-D images of object/scene for 3-D image reconstruction, was developed based on triangulation technique.